# Yahoo Web Search

1. Sort by

1. ### PreCalculus - Binomial Theorem: Find the coefficient of x^8 in the expansion (x^2+3)^7?

Well in this case the formula would be (n C n-j)*a^(n-j)*(x^2)^j x^8 = (x^2)^4 so j = 4 n = 7 n - j = 3 a = 3 So the...

2 Answers · Science & Mathematics · 26/07/2009

2. ### Determine whether the series sum(j=1 to inf) (-1)^j+1 j+3/j+10....what do I do here? I need step by step inst?

Assuming that |a(n)| = (j+3) / (j+10), this series diverges by the nth term test, because lim(j→∞) (j+3) / (j+10) = 1, which is nonzero. I hope this helps!

1 Answers · Science & Mathematics · 06/03/2013

3. ### A couple proofs about matrices and vectors?

...a_(1, j) * x_j , Σ(j=1 to n) a_(2, j) * x_j , ..., Σ(j=1 to n) a_(n, j) * x_j) Therefore, f(x) = x₁ Σ(j=1 to n) a_(1, j) * x...

1 Answers · Science & Mathematics · 12/10/2011

4. ### Analysis proof help!!?

Note that for n, j >0 : |a[n+j] - a[n]| < | a[n+j] - a[n+j-1]| + | a[n+j-1] - a[n+j-2...

1 Answers · Science & Mathematics · 30/09/2012

5. ### Binomial Theorem help please!?

... terms of the binomial expansion of (a + b)^n are C(n,j) * a^(n - j) * b^j Since we want the term for t^8 then n - j = 8. Given n...

3 Answers · Science & Mathematics · 18/08/2009

6. ### Precalculus - 15th term of (2x+y)^17?

The binomial theorm: n Σ n!/j!(n-j)! x^(n-j) a^j = (x+a)^n j=0 --------------------------------------------- The 15th term, will be j=15-1=14...

3 Answers · Science & Mathematics · 02/05/2013

7. ### Write down the term in x^4 from the expansion of (1-2x)^12?

... the binomial theorem ...................n (a + b)^12 = Σ C(n, j) a^(n - j) b^(j) ...................j=0 In this case a=1, b = -2x, and n=12. The...

2 Answers · Science & Mathematics · 17/10/2008

8. ### Math help! I need some help in Algebra? (10 points)?

I'm not very sure, but if none of the other answers on here work, seach on google... "letter equation" or "variable equation" and see what comes up.

3 Answers · Science & Mathematics · 28/09/2009

9. ### Prove 4^n = (sum from j=0 to n)(nCj)(3^j)?

...the Binomial Theorem: (a + b)^n = sum(j=0 to n) nCj * a^(n - j) * b^j. If we let a = 1 and b = 3 (a should be 1 to eliminate the n - j exponent...

2 Answers · Science & Mathematics · 07/08/2010

10. ### I need help with these algebra equationes?

(a + b )^n has jth term C(n,j) a^(n - j) b^j , C(n, j ) = n! / [ j! ( n-j)! ]...j = 0,1,2,...n ; use it.. note : 3rd term is when j = 2

1 Answers · Science & Mathematics · 10/03/2015